Surface Analytical Characterization of P3HT-Streptavidin Bilayers for Biosensing Applications. Issue 1795 (2015) - Sportelli, Maria Chiara; Picca, Rosaria Anna; Manoli, Kyriaki; Magliulo, Maria; Re, Marilena; Pesce, Emanuela; Tapfer, Leander; Santacroce, Maria Vittoria; Di Franco, Cinzia; Cioffi, Nicola; Torsi, Luisa
ABSTRACT: Ultrasensitive biosensors based on bottom gate organic field-effect transistors can be developed by depositing a functional biological (protein) interlayer directly on the silicon oxide gate dielectric and underneath the organic semiconductor film. However, the deposition methods for assembling the protein biological recognition layer can affect the biosensor analytical performances for the target analyte detection. Here, spin-coating and layer-by-layer techniques were considered as different approaches for streptavidin protein deposition. X-ray photoelectron spectroscopy (XPS) was systematically used in the non-destructive parallel angle resolved mode to characterize the multilayer device at each step of its assembly to gain information on elemental depth profiles. Scanning electron and scanning Helium ion microscopies gave information about stacked layer structure and morphology corroborating XPS results.